Civil responsibility of Physical Education professionals - Júlio Cezar Fernandes da Silveira (Journal of Physical Education (Maringá), 2008)
The aim of this paper is to analyze the civil responsibility of Physical Education professionals which consists of an obligation to repair eventual damages in their professional practice. Firstly, this study presents a historical rescue, the conceptualization of civil responsibility , the differentiation of that criminal responsibility, and also of the assumed ones. Secondly, the conditions for the imputation of a damage and the differentiation between obligation of means and obligation of results. Finally, the responsibilities and the duties of Physical Education professionals are presented. Due to inexhaustible situations which these professionals could be responsible for within a vast area area of performance, this paper searched for limiting the analysis to the professional responsibility outside school scope.